Development of a loop-mediated isothermal amplication assay for rapid detection of Escherichia coli O157: H7 bacteria - Hiep, Hoang Phu; Huan, Le Quang (Academia Journal of Biology, 2012)
Escherichia coli O157:H7 is a significant cause of foodborne illnesses and deaths in worldwide. A rapid and sensitive detection technique, which required to detect E. coli O157:H7 in foods, is the important and indispensable. Shiga toxin 2 (encoded by stx2) is important virulence factor for STEC strains and E. coli O157:H7 bacteria, therefore stx2 gene is the target gene for many detection techniques. In this study, we developed the loop mediated isothernal amplification (LAMP) method for rapid and sensitive detection of E. coli O157:H7 strains. The method advantages include rapidity, sensitivity and minimal equipment requirement. Primers were specially designed for founding on stx2 gene. The LAMP rection carries out in the thermocycler or waterbath. We recognize no difference when used oly inner primers (BIP/FIP) or 4-6 primers. A positive rection was visualied when used SYBR green stain or under UV light.